An easy classification for dental cervical abrasions - Madhuri Alankar Sawai (Wolters Kluwer Medknow Publications, 2014)
Introduction: Tooth wear - attrition, abrasion, or erosion - are modern day problems for dentistry. It usually leads to discomfort and sensitivity especially during eating, drinking, or tooth brushing. If left untreated for a long time, it may lead to loss of vitality of tooth. Various qualitative and quantitative methods have been used in the past to describe tooth wear. However, each method has certain shortfalls. There is no ideal index that is simple and clear in its scoring criteria. The Hypothesis: The classifications described in the literature are very descriptive and hence, it takes a long time to grade for a complete dentition. Some are based on the morphologic appearance and others on severity. A classification system has to facilitate standardized identification of a condition and help in diagnosis and treatment planning. The present manuscript is an attempt to emphasize the need to develop a classification system that is easy to score and describes the condition in details without utilizing much time. Evaluation of the Hypothesis: The hypothesis highlights some drawbacks of the classification systems available today and puts forth a new and easy to use classification system.